FEVER IN CHILDREN WITH RESPIRATORY VIRAL INFECTIONS: EFFECTIVE AND SAFE METHODS OF TREATMENT - T. E. Taranushenko; V. N. Panfilova (Вопросы современной педиатрии, 2013)
One of the most important — the problem of treatment of fever in children with respiratory viral infections — is discussed in this article. It is fever as one of the first symptoms of disease which often frightens parents and leads to inappropriate and excess usage of antipyretic agents, which in its turn can cause unfavorable consequences. The authors represent their own data on frequency of antipyretic drugs usage in children with respiratory viral infections, as well as the answers of pediatricians to the questionnaires on methods of choice in temperature normalization. According to the modern Russian as well as European and American clinical guidelines on treatment of fever in children the management of selection of patients demanding antipyretic treatment is detailed, indications and contraindications to such therapy are described, the most effective methods of temperature normalization in children with acute respiratory infection are discussed. The authors suggested the data on recommended dosages of paracetamol, which were revised in 2011 by the UK Medicines Control Agency, to be very useful. The current information on advantages of ibuprofen in comparison to paracetamol in treatment of fever in children with respiratory viral infections is shown. The main target of this article is understanding and acceptance by pediatricians of the modern recommendation on differential and reasonable approach to administration of antipyretic drugs in children with respiratory viral infections.